Obtenção de modelos estruturais de carbonos ativados utilizando dinâmica molecular reativa - Gonçalves, Rafael Vasconcelos (2019)
Carbons are versatile nanoporous materials that are useful in adsorption separation processes and catalysis. Its amorphous nature combined with the lack of high level visualization of structural elements by microscopy techniques makes the structural analysis of these materials a challenging task. In order to obtain a structural model free of any empirical aspects, molecular simulations were performed using reactive molecular dynamics to recreate the oxidative etching of carbon sheets during the activation process. In these simulation it was possible to obtain structures that are 10% and 25% etched, which is related to the number of atoms removed, on two diferent systems: basal and vertical. After being etched, such structures go through an annealing process to reorganize the atoms in a stable way. The simulations shows the evolution of the carbon atom removal process and the characteristics of the resulting models. The results obtained are consistent with microscopy images from the literature. Furthermore, the adsorptive properties of these models showed a better fitting to real carbon materials than other implicit models.